Preparation of Ultrathin 2D MoS2/Graphene Heterostructure Assembled Foam-like Structure with Enhanced Electrochemical Performance for Lithium-ion Batteries. (10th July 2016) - Liu, Hui; Chen, Xianjin; Deng, Lu; Su, Xing; Guo, Kai; Zhu, Zhenfeng
Abstract: A simple one-step surfactant-free hydrothermal approach is presented for the facile synthesis of ultrathin 2D MoS2 /graphene heterostructure (rGO@MoS2 ) assembled foam-like structure. The morphology and structure of the rGO@MoS2 nanocomposite are characterized by scanning electron microscopy (SEM), transmission electron microscopy (TEM), X-ray diffraction (XRD), Raman spectra, X-ray photoelectron spectroscopy (XPS) and Fourier transform infrared spectroscopy (FT-IR). It is found that numerous of ultrathin MoS2 nanosheets are homogeneously self-assembled on the surface of the foam-like reduced graphene oxide which acts as the skeleton of the nanocomposite. The electrochemical performance of the composite electrode is investigated. Due to countless exposed active sites of the ultrathin 2D MoS2 nanosheets and rapid ion diffusion and electron transport of the foam-like reduced graphene oxide with high strength and large specific surface area, the rGO@MoS2 composite shows superior electrochemical performance based on the cycling stability (retaining 657 mAh g −1 after 150 cycles while retaining 110 mAh g −1 after only 60 cycles of MoS2 ), and specific capacity (achieving more than 786 mAh g −1 at 100 mA g −1 ) compared with the pure MoS2 when used as electrode materials in LIBs.